2019
DOI: 10.1002/nau.24170
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 MAP kinase signaling pathways in storage and voiding dysfunction in mice with spinal cord injury

Abstract: Aim: To investigate the role of p38 MAP kinase in lower urinary tract dysfunction in mice with spinal cord injury (SCI). Methods: Cystometry and external urethral sphincter-electromyography were performed under an awake condition in 4-week SCI female mice. Two weeks after SCI, a catheter connected to an osmotic pump filled with a p38 mitogen-activated protein kinase (MAPK) inhibitor or artificial cerebrospinal fluid (CSF) was implanted into the intrathecal space of L6-S1 spinal cord for continuous intrathecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
5
2
Order By: Relevance
“…It has been reported that anti‐NGF treatment with NGF antibodies significantly decreased NVCs in SCI female mice 18 . Furthermore, it has been demonstrated that SCI‐induced detrusor overactivity is induced at least in part by hyperexcitability of C‐fiber bladder afferent pathways and that increased levels of TRPV1, which is predominantly expressed in C‐fiber bladder afferent neurons in L6‐S1 DRG, are involved in C‐fiber afferent hyperexcitability following SCI 4,19,20 . However, the current study did not show any significant differences in TRPV1 in L6‐S1 DRG or NGF‐β levels in the bladder between male and female SCI mice while higher numbers of NVCs were observed in male SCI mice than in female SCI.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…It has been reported that anti‐NGF treatment with NGF antibodies significantly decreased NVCs in SCI female mice 18 . Furthermore, it has been demonstrated that SCI‐induced detrusor overactivity is induced at least in part by hyperexcitability of C‐fiber bladder afferent pathways and that increased levels of TRPV1, which is predominantly expressed in C‐fiber bladder afferent neurons in L6‐S1 DRG, are involved in C‐fiber afferent hyperexcitability following SCI 4,19,20 . However, the current study did not show any significant differences in TRPV1 in L6‐S1 DRG or NGF‐β levels in the bladder between male and female SCI mice while higher numbers of NVCs were observed in male SCI mice than in female SCI.…”
Section: Discussioncontrasting
confidence: 84%
“…18 Furthermore, it has been demonstrated that SCI-induced detrusor overactivity is induced at least in part by hyperexcitability of C-fiber bladder afferent pathways and that increased levels of TRPV1, which is predominantly expressed in C-fiber bladder afferent neurons in L6-S1 DRG, are involved in C-fiber afferent hyperexcitability following SCI. 4,19,20 However, the current study did not show any significant differences in TRPV1 in L6-S1 DRG or NGF-β levels in the bladder between male and female SCI mice while higher numbers of NVCs were observed in male SCI mice than in female SCI. Thus, this sex difference in detrusor overactivity might be related to other factors, for example, bladder ischemia due to bladder outlet obstruction in male SCI mice 21 although further studies need to be performed to clarify this point.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations